Qualidade de vida e vivência da dor crónica nas doenças reumáticas [Health related quality of life and chronic pain experience in rheumatic diseases] - Paula Oliveira (2009)
Objectives: To assess differences among, health-related quality of life, pain threshold and perception, and passive coping strategies with chronic pain (specifically retreating, worrying, and resting), as well as associations among variables in three groups of rheumatic patients-fibromyalgia (FM), rheumatoid arthritis (RA), and osteoarthritis (OA). Material and methods: 86 participants diagnosed with FM (n = 25), RA (n = 31) and OA (n = 30) completed the following measures: Clinical and Socio-demographic Questionnaire (QSDC), Medical Outcomes Study 36-item Short Form Health Survey (SF-36v2), Pain Coping Inventory (PCI), visual analogic scale (VAS) for pain, and dolorimeter for threshold pain. SPSS software was used to perform statistical analyses. Results: FM patients reported the lowest levels of quality of life and threshold pain, as well as the highest levels of pain perception and passive coping with chronic pain. Associations between variables support that experience with chronic pain is managed more successfully in OA patients, followed by RA patients and, finally, by FM patients. Conclusions: Our findings support the adoption of a biopsychosocial model for assessment and intervention with rheumatic patients, considering specificities associated to each illness.